The Behavior of Glued-in Threaded Steel Rod Joints in Bangkirai Timber Beams under Flexural Loading: Experimental and Numerical Investigations - Awaludin, Ali; Akbar, Miqdad Khosyi (Journal of Engineering and Technological Sciences, 2026)
This study investigated flexural performance of Bangkirai timber beams jointed with glued-in threaded steel rods using epoxy-resin adhesive through experimental test and numerical analysis. Six beam specimens were tested under four-point bending with varying rod diameters, anchorage lengths, and beam widths: GIR B.65.16.17 (65 mm width, 16 mm rod, 170 mm anchorage), GIR B.65.12.25 (65 mm width, 12 mm rod, 250 mm anchorage), and GIR B.110.12.25 (110 mm width, 12 mm rod, 250 mm anchorage). The results showed that anchorage length significantly influenced moment capacity and stiffness of the beams. The highest average moment capacity was in GIR B.110.12.25 at 20.08 kNm due to its larger cross-section, while GIR B.65.12.25 showed a 58% higher moment capacity (16.57 kNm) than GIR B.65.16.17 (10.48 kNm). Elastic stiffness values were 538.60 kNm2, 809.44 kNm2, and 948.01 kNm2 in GIR B.65.16.17, GIR B.65.12.25, and GIR B.110.12.25, respectively, with longer anchorage lengths enhancing stiffness. The primary failure mechanism was epoxy-resin bond failure, leading to beam separation, while pull-out failure of steel rods was observed in some cases, particularly in specimens with shorter anchorage lengths. A 3-D nonlinear FEA was developed to validate experimental results. Differences between experimental and FEA results were within acceptable ranges, including 0.6-14.6% for elastic stiffness and 8.1-13.7% for moment capacity. Load-displacement curves obtained from the FEA correlated well with the experimental results, although the model slightly overestimated moment capacity due to the assumption of perfect bonding. These results provided insights for optimizing glued-in rod timber joints in structural applications.